Análisis de la Extensión Github Copilot, en el ámbito de colaboración hacia los desarrolladores, para aumentar, la eficacia en el desarrollo de proyectos. - Lata Jácome, Kevin Baltazar (2023)
This project focuses on conducting a detailed analysis of the GitHub Copilot extension, with a focus on its application in developer collaboration. The main objective is to evaluate how GitHub Copilot can enhance efficiency in software project development. Key features, advantages, and potential limitations of GitHub Copilot will be explored. Additionally, tests will be conducted to measure its impact on collaboration and project development. This analysis will provide a deep understanding of how GitHub Copilot can benefit development teams and its role in the evolution of programming.